Dynamic Fair Dealing: Creating Canadian Culture Online - ROSEMARY J. COOMBE, DARREN WERSHLER, dan MARTIN ZEILINGER (University of Toronto Press, 2014)
The call for the papers that comprise this volume began as a manifesto: a call to arms for academics, artists, and activists to defend Canadaâ€™s emerging digital culture. We posed a series of queries, declarations, and provocations that distilled into a single question: given the legal, social, and practical contours of cultural life in a digital era, how can we collectively ensure that digital technologies best serve the creative and social needs of Canadians? To answer this question, we need to better understand the activities and aspirations that animate the work that Canadians actually do in digital environments. We are all aware that networked digital technologies provide significant tools and unique opportunities for democratically transforming cultural life. Nonetheless, as critics such as Darin Barney (2000) remind us, the progressive possibilities of such technologies are not inherent, but shaped by their social regulation. Thus, our manifesto: The process of â€œdealingâ€ itself â€“ that is, the dynamic, complex, contingent, and shifting set of relationships and practices characteristic of the space between digital cultural creation and regimes of law and social regulation â€“has eluded the attention of scholars for too long. This is not surprising, because the fair dealing provisions in Canadaâ€™s Copyright Act have been â€œpoorly applied and underusedâ€ (Handa 2002: 288). Dealing with cultural goods and conducting social negotiations about their propriety shapes the quality and experience of digital culture in Canada. What constitutes â€œfairnessâ€ within digital networks is constantly and contextually evolving, and demands a greater degree of attention than we currently afford it. Critics, activists, librarians, scholars, creators, and citizensâ€™ groups everywhere are embroiled in complex debates over intellectual property (IP) rightsâ€™ extensions, corporate enforcement practices, and exercises of digital rights management. Many believe that as forms and exercises of power, such attempts to extend the reach of IP rights are illegitimate, excessive, or simply out of step with the realities of contemporary cultural expression, production, and exchange in digital environments. In short, despite the capacity for collaborative creation that digital technology affords, and despite the ostensible commitment from all levels of government to make Canadian cultural content more accessible, IP laws in Canada pose unnecessarily punitive prospects for potential liability.